2016
DOI: 10.1371/journal.pone.0146229
|View full text |Cite
|
Sign up to set email alerts
|

Piscine Orthoreovirus from Western North America Is Transmissible to Atlantic Salmon and Sockeye Salmon but Fails to Cause Heart and Skeletal Muscle Inflammation

Abstract: Heart and skeletal muscle inflammation (HSMI) is a significant and often fatal disease of cultured Atlantic salmon in Norway. The consistent presence of Piscine orthoreovirus (PRV) in HSMI diseased fish along with the correlation of viral load and antigen with development of lesions has supported the supposition that PRV is the etiologic agent of this condition; yet the absence of an in vitro culture system to demonstrate disease causation and the widespread prevalence of this virus in the absence of disease c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
150
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(181 citation statements)
references
References 33 publications
15
150
2
2
Order By: Relevance
“…Higher PRV-2 RNA loads (> 1.0 × 10 10 L2 RNA/100 μL PB or 100 mg tissue) were found in these tissues in the diseased fish (either artificially or naturally infected with EIBS). Similarly, in a previous study of PRV, the blood, spleen, and kidney had the highest viral RNA loads of the 11 tissues tested in HSMI-affected Atlantic salmon [29]. It is generally understood that erythrocytes are the target cells of both PRV species (causative agents of EIBS and/or HSMI), because they form inclusion bodies in these cells [2, 7, 8, 12, 14, 30, 31].…”
Section: Discussionmentioning
confidence: 71%
“…Higher PRV-2 RNA loads (> 1.0 × 10 10 L2 RNA/100 μL PB or 100 mg tissue) were found in these tissues in the diseased fish (either artificially or naturally infected with EIBS). Similarly, in a previous study of PRV, the blood, spleen, and kidney had the highest viral RNA loads of the 11 tissues tested in HSMI-affected Atlantic salmon [29]. It is generally understood that erythrocytes are the target cells of both PRV species (causative agents of EIBS and/or HSMI), because they form inclusion bodies in these cells [2, 7, 8, 12, 14, 30, 31].…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, although infection with PRV is common in farmed Atlantic salmon in BC, disease manifestations impacting fish performance as observed in Norway has never been reported (reviewed in [16]). Using injection and cohabitation challenge trials, we recently examined the infectivity and pathogenicity of PRV from the west coast of North America to Atlantic and Sockeye salmon ( Oncorhynchus nerka ) and whether infection would result in HSMI [17]. We demonstrated that PRV was capable of infecting, replicating and persisting within both host species over a 41 week period yet histopathological signs of HSMI were not observed.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that PRV was capable of infecting, replicating and persisting within both host species over a 41 week period yet histopathological signs of HSMI were not observed. As with infections associated with HSMI, these non-pathogenic infections showed a similar blood cell tropism and comparable infection dynamics, suggesting that PRV is of low virulence to Atlantic and Sockeye salmon in western North America [17]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations